2020
DOI: 10.1101/2020.10.09.332833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial precursors and unsaturated long-chain fatty acids are biomarkers of North-Atlantic demosponges

Abstract: Sponges produce distinct fatty acids (FAs) that (potentially) can be used as chemotaxonomic and ecological biomarkers to study endosymbiont-host interactions and the functional ecology of sponges. Here, we present FA profiles of five common habitat-building deep-sea sponges (class Demospongiae, order Tetractinellida), which are classified as high microbial abundance (HMA) species. Geodia hentscheli, G. parva, G. atlantica, G. barretti, and Stelletta rhaphidiophora were collected from boreal and Arctic sponge g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In addition, a high percentage of their population participated in reproduction, as also mentioned for G. cydonium (Mercurio et al, 2007). So, despite the scarcity of nutrients in these habitats throughout the year, these species seemed to have a high reproductive effort, that together with their interplay with microbial symbionts (Radax et al, 2012;De Kluijver et al, 2020) could explain the dense aggregations of these species in the sponge grounds. This pattern contrasts to the theory that deep-sea benthos has usually a low reproductive effort due to unfavorable abiotic conditions, such as lack of nutrients (e.g., Thorson, 1950).…”
Section: Reproductive Strategy and Sex Ratio: Commonalities And Diffementioning
confidence: 70%
See 1 more Smart Citation
“…In addition, a high percentage of their population participated in reproduction, as also mentioned for G. cydonium (Mercurio et al, 2007). So, despite the scarcity of nutrients in these habitats throughout the year, these species seemed to have a high reproductive effort, that together with their interplay with microbial symbionts (Radax et al, 2012;De Kluijver et al, 2020) could explain the dense aggregations of these species in the sponge grounds. This pattern contrasts to the theory that deep-sea benthos has usually a low reproductive effort due to unfavorable abiotic conditions, such as lack of nutrients (e.g., Thorson, 1950).…”
Section: Reproductive Strategy and Sex Ratio: Commonalities And Diffementioning
confidence: 70%
“…A recent study, not yet peer-reviewed, has showed that bacterial symbionts of Geodia spp. (including G. barretti, G. hentscheli, and G. atlantica), provide the host with precursor lipid building blocks, contributing to the synthesis of sponge unsaturated long-chain fatty acids (De Kluijver et al, 2020). So, the high content in lipid yolk might be related to the presence of high microbial abundance in these species, and it might be the case that by-products of bacterial symbionts within the oocytes contribute to the "autosynthetic" activity of lipid formation.…”
Section: Reproductive Strategy and Sex Ratio: Commonalities And Diffementioning
confidence: 99%